Synthesis, crystal structure, Hirshfeld surface and interaction energies analysis of 5-methyl-1,3-bis(3-nitrobenzyl)pyrimidine-2,4(1H,3H)-dione - Etse, Koffi Senam; Lamela, Laura Comeron; Zaragoza, Guillermo; Pirotte, Bernard (European Journal of Chemistry, 2020)
The title compound 5-methyl-1,3-bis(3-nitrobenzyl)pyrimidine-2,4(1H,3H)-dione was obtained by reaction of thymine with 3-nitrobenzylbromide in the presence of cesium carbonate. Characterization of the product was achieved by NMR spectroscopy and its stability was probed in basic condition using UV-Visible analysis. Furthermore, the molecular structure was confirmed by X-ray diffraction analysis. The compound crystallizes in orthorhombic Pna21 space group with unit cell parameters a = 14.9594 (15) Å, b = 25.711 (3) Å, c = 4.5004 (4) Å, V = 1731.0 (3) Å3 and Z = 4. The crystal packing of the title compound is stabilized by intermolecular hydrogen bond, π···π and C−H···π stacking interactions. The intermolecular interactions were furthermore analyzed through the mapping of different Hirshfeld surfaces. The two-dimensional fingerprint revealed that the most important contributions to these surfaces come from O···H (37.1%), H···H (24%) and H···C/C···H (22.6%) interactions. The interaction energies stabilizing the crystal packing were calculated and were presented graphically as framework energy diagrams. Finally, the energy-framework analysis reveals that π···π and C−H···π interactions energies are mainly dispersive and are the most important forces in the crystal.